Asbestos risk in archaeology - Bianchi, Claudio; Bianchi, Tommaso (La Medicina del Lavoro, 2014)
Asbestos has been used since prehistoric times (1). The most ancient relics date back to about 4,000 BC; in the Savo area, south-eastern Finland, asbestos (antophyllite) was used in making pottery (4). Asbestos clothes found in some tombs of several sites in Thailand date back to the Neolithic and Bronze Ages (2)....